2018
DOI: 10.1007/s10911-018-9396-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiological, Histological and Chemical Analysis of Breast Microcalcifications: Diagnostic Value and Biological Significance

Abstract: Classification of mammary microcalcifications is based on radiological and histological characteristics that are routinely evaluated during the diagnostic path for the identification of breast cancer, or in patients at risk of developing breast cancer. The main aim of this study was to explore the relationship between the imaging parameters most commonly used for the study of mammary microcalcifications and the corresponding histological and chemical properties. To this end, we matched the radiographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 23 publications
2
45
0
1
Order By: Relevance
“…Our results clearly indicate that elemental composition, but not morphological appearance, of breast microcalcifications can predict the presence or development of bone metastatic lesions. In particular, according with the data reported by Bonfiglio et al [15] , in this study the breast cancer lesions of BM+ patients were frequently characterized by the presence calcifications made of MgHAp. Thus, the presence of MgHAp could play an active role in breast cancer progression.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our results clearly indicate that elemental composition, but not morphological appearance, of breast microcalcifications can predict the presence or development of bone metastatic lesions. In particular, according with the data reported by Bonfiglio et al [15] , in this study the breast cancer lesions of BM+ patients were frequently characterized by the presence calcifications made of MgHAp. Thus, the presence of MgHAp could play an active role in breast cancer progression.…”
Section: Discussionsupporting
confidence: 77%
“…In the last years, numerous studies highlighted the role of breast microcalcifications in the pathophysiogenesis of both breast cancer occurrence and progression [3][4][5][6]15,16] . In particular, we recently demonstrated the presence of breast cancer cells with an osteoblast phenotype (breast osteoblast-like cells- BOLCs) able to product microcalcifications made of HA or MgHAp [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Reports showing a positive correlation between PTX3 expression and poor prognosis in specific human tumors suggest that the role of PTX3 may be very dependent on tissue, cancer type and from the cellular source [62][63][64]. Our results showed an over-expression of PTX3 in PCs, compared to BL, suggesting therefore its possible involvement in tumor progression.…”
Section: Discussionsupporting
confidence: 58%
“…To better characterize the inflammatory response associated with prostatic lesions, it has been investigated the expression of an inflammation-associated molecule: PTX3. Recent studies have shown that PTX3 may have a prooncogenic role in some cancers, including ovary and lung cancer, prostate carcinoma, pancreatic carcinoma, and bone metastasis from breast cancer [61][62][63]. However, some studies report a protective role of PTX3 against cancer [64].…”
Section: Discussionmentioning
confidence: 99%
“…Most breast calcifications visible at mammography are made of a combination of calcium and phosphate, the exact composition of the mineral part of bones. Moreover, evidences of osteoblast-like cells in breast tissue suggest a potential for breast cells differentiation in a microcalcification environment [37,[95][96][97][98][99][100][101][102][103]. In 2005, Morgan et al [99] reported that microcalcifications were responsible for increasing the mitogenesis properties of breast cells, resulting in an amplification of the malignant process.…”
Section: Sfrp1 and Microcalcificationsmentioning
confidence: 99%